Sire evaluation using REML and conventional methods for first lactation 300 day milk yield in Phule Triveni cattle - AMBHORE, G S; SINGH, AVTAR; DEOKAR, D K; SINGH, MANVENDRA; PRAKASH, VED; SAHOO, S K (The Indian Journal of Animal Sciences, 2018)
The present study was undertaken to estimate the breeding values of 55 Phule Triveni sires for first lactation 300 day or less milk yield (FL300DMY) by using four different sire evaluation methods/models viz. Least Squares (LS), Simple Regressed Least Squares (SRLS), Best Linear Unbiased Prediction-Sire model (BLUP-SM) and Restricted Maximum Likelihood Method (REML). The REML method produced lowest error variance for FL300DMY and it was considered to be the most efficient method. The BLUP-SM method was second efficient followed by SRLS and LS methods. The estimated breeding values of sires for FL300DMY under study showed large variation between estimated breeding values of sires which revealed more genetic variation in the herd.